Injuries and well-being among adolescents in Finland from 2013 to 2021 - Korpilahti, Ulla; Koivisto, Mari; Partonen, Timo; Haikonen, Kari; Hakulinen, Tuovi; Lillsunde, Pirjo; Rautava, Päivi; Koivusilta, Leena (Oxford University Press (OUP), 2026)
Injuries lead to heath loss, disability, and significant costs. The aim of this study was to evaluate self-reported home and leisure injuries outside school by the 8th and 9th graders in Finnish secondary schools, and potential explanatory factors associated with their injuries. Data were gathered on 383 550 pupils in cross-sectional surveys (every second school year) done between years 2013 and 2021. Associations between injuries and the explanatory variables were assessed using logistic regression analysis. Bronfenbrenner’s bioecological model and the KINDL-R health-related quality of life measurement were used as the framework for this study. Nearly a third of the respondents (n = 120 494, 31.4%) had been injured one or more times during leisure time or at home. The most common injuries among all respondents were sport-related injuries (19.8%), other injuries sustained during leisure time (13.8%) and at home or nearby (9.4%). The use of safety equipment was quite low. The potential risk for injuries was highest among those who were severely anxious, those who often consumed enough alcohol to become heavily drunk, those who had tried or used drugs before, and adolescents of foreign background who had been born abroad. Adolescents with no close friends had a lower association with injury. Boys were more likely to sustain injuries than girls. Injuries suffered in leisure time and at home were linked to risky behaviour, emotional well-being, social and family relationships, and housing. Professionals in preventive work need to take the complex factors behind injuries into account.